Dual HCP structures formed in senary ScYLaTiZrHf multi-principal-element alloy. (February 2016) - Takeuchi, A.; Amiya, K.; Wada, T.; Yubuta, K.
Abstract: A senary ScYLaTiZrHf alloy was investigated for its ability to form a solid solution with an hcp structure, also known as a high-entropy alloy (HEA). X-ray diffraction analysis of the ScYLaTiZrHf alloy produced by arc-melting method confirmed this hcp structure. The microstructure of the ScYLaTiZrHf was composed of dual phases that were enriched in (Y, La) or (Ti, Zr, Hf), with Sc distributed evenly across both phases. The positive mixing enthalpy of 11.4 kJ mol −1 derived from Miedema's model, and the immiscible tendencies of its constituent binary phase diagrams help to explain the presence of dual phases in the ScYLaTiZrHf alloy. When formed into dual hcp solid solutions, the ScYLaTiZrHf alloy can be more accurately described as a multi-principal-element alloy (MPEA) rather than as a HEA, since the ScYLaTiZrHf alloy is a solid solution that is enthalpy-driven instead of entropy driven. The results also disclosed another procedure to stabilize solid solutions excepting for high-entropy scheme. Highlights: Dual hcp structures form in ScYLaTiZrHf alloy comprising transition metals mainly. The ScYLaTiZrHf alloy is regarded as a multi-principal-element alloy. The ScYLaTiZrHf alloy is a prototypical high-entropy alloy with hcp structure.